5B.02: LONGITUDINAL CHANGES IN LEFT VENTRICULAR DIASTOLIC FUNCTION IN A GENERAL POPULATION. (June 2015) - Kuznetsova, T.; Thijs, L.; Knez, J.; Cauwenberghs, N.; Petit, T.; Gu, Y.M.; Zhang, Z.; Staessen, J.A.
Abstract : Objective: Data on changes in left ventricular diastolic function (LVDF) over time in the general population are sparse. We, therefore, investigated in the population cohort clinical correlates of longitudinal changes in Doppler diastolic indexes analyzed as continuous measures and assessed factors predictive of the changes in LVDF grades over time. Design and method: We measured early and late diastolic peak velocities of mitral inflow (E and A) by conventional Doppler, and the mitral annular velocities (e' and a') by Tissue Doppler Imaging (TDI) in 650 participants (mean age 50.7 years) at baseline and after 4.7 years (5th to 95th percentile, 3.7—5.4). Results: In stepwise regression, the multivariable-adjusted correlates of the change in the transmitral and TDI diastolic indexes included sex, age, baseline serum insulin, blood pressure (BP) and heart rate. Over follow-up, LVDF grades remained unchanged in 87.2% (95% CI, 84.6% to 89.8%), improved in 3.7% (95% CI, 2.25% to 5.15%) and worsened in 9.1% (95% CI, 6.9% to 11.3%). Baseline age was a strong predictor of worsening of LVDF from normal/mild grade to more advanced grade (OR = 3.22; P < 0.0001). A doubling of baseline insulin was associated with a 184% increase in the odds of worsening of LVDF (P < 0.0001). Moreover, baseline diastolic BP and the change in systolic BP over time predicted worsening of LVDF (P < 0.014). Conclusions: The key findings of this study are that LVDF tended to worsen over time and was associated with advanced age, higher baseline insulin level and hemodynamic parameters such as heart rate and BP.